(untitled) (Eurasian Journal of Engineering and Technology, 2023)
In this articleways to achieve energy savings during the operation of an asynchronous electric motor are described. The method of using an asynchronous electric motor for the purpose of energy saving of electricity is described. Analysis of the energy saving potential that significant savings in electrical energy can be obtained by improving the efficiency of the asynchronous motor